Making Guidance of Financial Reports Using the Application and Improving Company Profile for B2b Promotion on Indonesia Leather Shoes MSMEs - Baskoro Ismail; Hasnul Suhami (Future Science, 2020)
According to the Ministry of Cooperatives and MSMEs of the Republic of Indonesia in 2017, MSMEs contribute to 99% of Indonesia’s total entrepreneurs and 97% of Indonesia’s total workers. One type of entrepreneur in Indonesia is the process industry which operates by processing raw material into consumer products. An example of this industry is the footwear industry. This paper aims to help one of the leather shoe MSMEs in Indonesia by making financial reports to analyze the performance of MSMEs and create a company profile for B2B promotion. Qualitative case study research, internal and external analysis, and business coaching methods are used to find actual conditions and gaps that exist, then take the implementation approved by MSMEs to resolve gaps in MSMEs. After conducting internal and external analysis such as Business Process, BMC, PESTLE, Porter's Five Forces, STP, 7Ps, and Financial Statement Analysis, it turns out the problems lies within the disorganized financial reports and disorganized company profiles that cannot be used as a promotional tool. Pareto and gap analysis found the most important and easiest problems to resolve. Therefore, reducing the gap in MSMEs by making guidance of financial reports using the application for MSME and improving company profiles for B2B promotion is needed.